Disorder-specific cingulo-opercular network hyperconnectivity in pediatric OCD relative to pediatric anxiety. Issue 4 (16th March 2023) - Becker, Hannah C.; Norman, Luke J.; Yang, Huan; Monk, Christopher S.; Phan, K. Luan; Taylor, Stephan F.; Liu, Yanni; Mannella, Kristin; Fitzgerald, Kate D.
Abstract: Background: Prior investigation of adult patients with obsessive compulsive disorder (OCD) has found greater functional connectivity within orbitofrontal–striatal–thalamic (OST) circuitry, as well as altered connectivity within and between large-scale brain networks such as the cingulo-opercular network (CON) and default mode network (DMN), relative to controls. However, as adult OCD patients often have high rates of co-morbid anxiety and long durations of illness, little is known about the functional connectivity of these networks in relation to OCD specifically, or in young patients near illness onset. Methods: In this study, unmedicated female patients with OCD (ages 8–21 years, n = 23) were compared to age-matched female patients with anxiety disorders ( n = 26), and healthy female youth ( n = 44). Resting-state functional connectivity was used to determine the strength of functional connectivity within and between OST, CON, and DMN. Results: Functional connectivity within the CON was significantly greater in the OCD group as compared to the anxiety and healthy control groups. Additionally, the OCD group displayed greater functional connectivity between OST and CON compared to the other two groups, which did not differ significantly from each other. Conclusions: Our findings indicate that previously noted network connectivity differences in pediatric patients with OCD were likely not attributable to co-morbid anxiety disorders. Moreover, these results suggest that specific patterns of hyperconnectivity within CON and between CON and OST circuitry may characterize OCD relative to non-OCD anxiety disorders in youth. This study improves understanding of network dysfunction underlying pediatric OCD as compared to pediatric anxiety.